2018
DOI: 10.1002/jgt.22360
|View full text |Cite
|
Sign up to set email alerts
|

Subdivisions of oriented cycles in digraphs with large chromatic number

Abstract: An oriented cycle is an orientation of a undirected cycle. We first show that for any oriented cycle C, there are digraphs containing no subdivision of C (as a subdigraph) and arbitrarily large chromatic number. In contrast, we show that for any C a cycle with two blocks, every strongly connected digraph with sufficiently large chromatic number contains a subdivision of C. We prove a similar result for the antidirected cycle on four vertices (in which two vertices have out‐degree 2 and two vertices have in‐deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
(36 reference statements)
0
22
0
Order By: Relevance
“…In this article, we improve the above upper bound (( + ) 4 ) to (( + ) 2 ) using a quite different approach from [6]. The following is our main result.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…In this article, we improve the above upper bound (( + ) 4 ) to (( + ) 2 ) using a quite different approach from [6]. The following is our main result.…”
Section: Introductionmentioning
confidence: 90%
“…We mention that a different extension of Bondy's theorem was obtained in [5]. Very recently, among other results, Cohen, Havet, Lochet, and Nisse [6] first obtained a finite upper bound of ( ) for strong digraphs containing no ( , ). Precisely, they proved the following.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The existence of subdivisions of 2-spindles has attracted some interest in the literature. Indeed, Benhocine and Wojda [4] showed that a tournament on n ≥ 7 vertices always contains a subdivision of a ( 1 , 2 )-spindle such that 1 + 2 = n. More recently, Cohen et al [9] showed that a strongly connected digraph with chromatic number Ω(( 1 + 2 ) 4 ) contains a subdivision of a ( 1 , 2 )-spindle, and this bound was subsequently improved to Ω(( 1 + 2 ) 2 ) by Kim et al [20], who also provided improved bounds for Hamiltonian digraphs.We consider two problems concerning the existence of subdivisions of 2-spindles. The first one is, given an input digraph G, find the largest integer such that G contains a subdivision of a ( 1 , 2 )-spindle with min{ 1 , 2 } ≥ 1 and 1 + 2 = .…”
mentioning
confidence: 99%